The exorcism stories in Luke-Acts: a sociostylistic reading - Klutz, Todd (Society for New Testament Studies monograph series, 2004)
This 2004 book in English integrates detailed literary criticism of the exorcism stories in Luke-Acts with wide-ranging comparative study of ancient sources on demonology, spirit affliction and exorcistic healing. Methods from systemic functional linguistics and critical theory are explained and then applied to each story. Careful focus is placed on each narrative's linguistic functions and also on relevant aspects of its literary co-text and the wider context of culture. Implications of the analysis for the new perspective on Luke-Acts, especially the implied author's relationship with Judaism, are explored in relation to the Lukan stories' original context of reception. Largely neglected interfaces between Luke's narrative representation of exorcism and emerging academic discourse about religious experience, shamanism, health care in antiquity, ritual performance and ancient Jewish systems of impurity are probed in ways that shed fresh light on this supremely alien part of the Lukan writings.